2016
DOI: 10.3892/ol.2016.4494
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of cathepsin L sensitizes ovarian cancer cells to chemotherapy

Abstract: Abstract. Ovarian cancer is a leading gynecological malignancy associated with high mortality. The development of acquired drug resistance is the primary cause of chemotherapy failure in the treatment of ovarian cancer. To examine the mechanism underlying paclitaxel resistance in ovarian cancer and attempt to reverse it, the present study induced a TAX-resistant ovarian cancer cell line, SKOV3/TAX. Cathepsin L (CTSL) has been found to be overexpressed in ovarian cancer. The aim of the present study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The elevated levels of CTSL might be associated to proliferation, invasion, metastasis and chemoresistance of cancer cells [18]. In addition, knockdown of CTSL could sensitize cancer cells to chemotherapy and target therapy [19,20]. Our study found that CTSL was up-regulated in gastric cancer compared to normal tissues, which is consistent with the ndings in previous studies [21].…”
Section: Discussionsupporting
confidence: 90%
“…The elevated levels of CTSL might be associated to proliferation, invasion, metastasis and chemoresistance of cancer cells [18]. In addition, knockdown of CTSL could sensitize cancer cells to chemotherapy and target therapy [19,20]. Our study found that CTSL was up-regulated in gastric cancer compared to normal tissues, which is consistent with the ndings in previous studies [21].…”
Section: Discussionsupporting
confidence: 90%
“…Zheng et al revealed that CTSL inhibition enhances the availability of cytoplasmic and nuclear protein drug targets, including estrogen receptor-α, Bcr-Abl, topoisomerase-IIα, histone deacetylase 1, and androgen receptor [9] . CTSL suppression also improves gefitinib resistance in non-small cell lung cancer [14] , and CTSL knockdown can increase the sensitivity of ovarian cancer cells to paclitaxel [38] . Our previous study also suggested that CTSL may be a novel therapeutic target to prevent tumor cells from becoming resistant to chemotherapy and to reinforce the efficiency of paclitaxel and cisplatin against lung cancer [12] .…”
Section: Discussionmentioning
confidence: 99%
“…10,15,25 Preclinical in vitro and in vivo studies have shown that CIP2A may regulate the proliferation, senescence, and apoptosis of multiple cancer cells [26][27][28] and contribute to resistance to chemotherapy such as cisplatin or docetaxel in solid tumors. [29][30][31] Therefore, CIP2A inhibition may serve as a promising modality to overcome chemoresistance. However, the role of CIP2A in radioresistance remains unclear, especially in HNSCC cells with p53 mutation.…”
Section: Discussionmentioning
confidence: 99%